A Systematic Literature Review of Digital Finance and Global Marketing - Bhenu Artha; Jumadi Jumadi; Utami Tunjung Sari; Ascasaputra Aditya; Bahri Bahri; Niken Permata Sari; Antonius Satria Hadi; Cahya Purnama Asri (Indonesia Economic Journal, 2026)
Digital finance and global marketing have emerged as transformative forces reshaping the contemporary economic landscape. This study presents a systematic literature review examining the intersection of these domains, analyzing 287 peer-reviewed articles published between 2019 and 2024 from reputable international databases. Following rigorous methodological protocols, the research synthesizes current trends, identifies key research gaps, and provides actionable insights for stakeholders. The results reveal a significant growth trajectory in scholarly attention, with publications increasing from 12 in 2019 to 45 in 2024. Key research focus areas include digital marketing strategies, digital payment systems, and consumer behavior. Findings indicate that successful organizations integrate multiple technologies—specifically Artificial Intelligence (AI), blockchain, and mobile payments—into comprehensive strategies rather than isolated adoptions. Consumer trust is identified as a critical mediator influencing adoption, while regulatory fragmentation and the digital divide remain substantial barriers to global implementation. The review concludes that sustainable competitive advantage derives from integrated and customer-centric innovation.